1992
DOI: 10.1007/bf00190067
|View full text |Cite
|
Sign up to set email alerts
|

Dermal and facial autografts in facial aesthetic surgery

Abstract: Results are presented of dermis grafts used in conjunction with surgery for aging changes in the face. During a two-year period grafts were used to correct crease lines in the glabella and nasolabial creases, as well as angles of the mouth and vermilion. Volume of the grafts was well maintained and very few complications occurred. This technique offers better long-term results than can be obtained by collagen or fat injections. The results and techniques are presented in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…40 Fascial grafts obtained from the face lift discard specimen are associated with no complications and may last longer than fat or dermis. 6,41 This is because of the rich collagen and fibrous tissue included in the fascia, but further studies must be conducted to clarify this hypothesis and also to compare performance between materials.…”
Section: Resultsmentioning
confidence: 99%
“…40 Fascial grafts obtained from the face lift discard specimen are associated with no complications and may last longer than fat or dermis. 6,41 This is because of the rich collagen and fibrous tissue included in the fascia, but further studies must be conducted to clarify this hypothesis and also to compare performance between materials.…”
Section: Resultsmentioning
confidence: 99%
“…The dermis of the lower abdomen is soft and elastic, and is almost impalpable after transplantation. If there is a requirement for a larger volume, the transplant site can be folded twice, and can be fixed with sophisticated catgut sutures or fibrin glue closure [4].…”
Section: Discussionmentioning
confidence: 99%
“…In 1960, Thompson (1 1) had biopsied specimens from patients up to five years after implantation and come to the same histological conclusion. Nicolle et al (6) showed that this complication is almost nonexistent if all obvious subcutaneous fat is trimmed off.…”
Section: Case Reportmentioning
confidence: 99%
“…Stark (10) stated that excessive absorption occurred in grafts more than 1 cm thick, which does not apply to pure dermal grafts. Some reports have shown fat preservation in humans as many as eight years after implantation (1) and Nicolle et al (6) suggested that loss of graft volume in dermal grafting during the initial six weeks is no more than loss of soft tissue swelling with revascularisation. It is far too early to say whether cyst formation and resorption will be a complication in this case.…”
Section: Case Reportmentioning
confidence: 99%